1995
DOI: 10.1111/j.1476-5381.1995.tb16358.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐lasting activation of cation current by low concentration of endothelin‐1 in mouse fibroblasts and smooth muscle cells of rabbit aorta

Abstract: 1 Recombinant human ETA receptors were expressed in a mouse fibroblast cell line (Ltk-cell) and functional coupling of the receptors with Ca24 permeable channels at low concentrations of endothelin-l (ET-1) was investigated using whole-cell recordings and monitoring the changes in intracellular free Ca2" concentrations ([Ca24] evoked an initial transient peak and a subsequent sustained elevation in [Ca24]i whereas a lower concentration of ET-1 (10-10 M) evoked only a sustained elevation of [Ca2"i. After remo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
54
1

Year Published

1998
1998
2003
2003

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 28 publications
5
54
1
Order By: Relevance
“…When one considers the possible role of ET-1 in mediating HPV, it is of some interest to note that endothelin receptor activation can induce constriction of arterial smooth muscle not only by raising the intracellular Ca 2+ concentration (Highsmith et al, 1992;Pang et al, 1989;Kasuya et al, 1989;Goto et al, 1989;Enoki et al, 1995), but by increasing the sensitivity of the contractile apparatus to Ca 2+ (Nishimura et al, 1992;Ohanian et al, 1997). The signi®cance of this observation becomes apparent when taken together with the fact that calcium sensitization has also been implicated in the development of HPV .…”
Section: Introductionmentioning
confidence: 99%
“…When one considers the possible role of ET-1 in mediating HPV, it is of some interest to note that endothelin receptor activation can induce constriction of arterial smooth muscle not only by raising the intracellular Ca 2+ concentration (Highsmith et al, 1992;Pang et al, 1989;Kasuya et al, 1989;Goto et al, 1989;Enoki et al, 1995), but by increasing the sensitivity of the contractile apparatus to Ca 2+ (Nishimura et al, 1992;Ohanian et al, 1997). The signi®cance of this observation becomes apparent when taken together with the fact that calcium sensitization has also been implicated in the development of HPV .…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism by which contractions are evoked by ET-1 in isolated vascular preparations is complicated. The increase in the sensitivity of the contractile apparatus to intracellular Ca 2+ ([Ca 2+ ] i ), as well as the increase of [Ca 2+ ] i concentration, may be involved in ET-1-induced vasoconstriction [8,26,28,29]. On the other hand, ET-1 evoked an increase of myofilament Ca 2+ sensitivity by a mechanism(s) independent of tyrosine kinase in the rat pulmonary artery [10].…”
mentioning
confidence: 99%
“…[Ca 2+ ] i was determined using the fluorescent probe fluo-3 instead of fura-2 as described previously (Enoki et al 1995;Iwamuro et al 1998), because LOE 908 was found to disturb measurement of [Ca 2+ ] i by absorbing the light at excitation wavelengths for fura-2. For loading of the probes, the cultured cells were incubated in Ca 2+ -free Krebs-HEPES buffer containing 5 µM fluo-3/acetoxymethyl ester for 45 min at 37°C.…”
Section: Measurement Of Cytosolic Free Calcium Concentrationmentioning
confidence: 99%
“…Immediately before measurement of [Ca 2+ ] i , CaCl 2 was added to the suspension at the final concentration of 1 mM, and 1-ml aliquots of the suspension were used for measurement of fluorescence by a CAF 110 spectrophotometer (JASCO, Tokyo, Japan). Wavelengths of excitation and emission for fluo-3 were 490 nm and 540 nm, respectively, and [Ca 2+ ] i was calculated as described previously (Enoki et al 1995). The ET-1-induced increases in [Ca 2+ ] i were determined by subtracting the basal [Ca 2+ ] i from the peak value following addition of ET-1, and unless otherwise specified, the data were expressed as the ET-1-induced increases in [Ca 2+ ] i .…”
Section: Measurement Of Cytosolic Free Calcium Concentrationmentioning
confidence: 99%
See 1 more Smart Citation